Biodiversity Conservation through the Ecological Approach of Philemon buceroides on Moyo Island, West Nusa Tenggara - Yamin, M.; Khairuddin, Khairuddin; Artayasa, I Putu (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2025)
The presence of endemic species is very important for ecosystem balance, scientific knowledge, and the identity of a region. Philemon buceroides is one of the endemic animals in West Nusa Tenggara (NTB). This paper analyzes its ecological aspects on Moyo Island and examines its role in supporting biodiversity conservation efforts. Data collection was conducted using survey and point observation methods across three habitat types: plantations, forest edges, and the interior forest. The data collected included food, habitat vegetation, associations, and predators. The results identified 51 species, of which 56.86% are used as sources of food, resting places, play areas, shelter, and breeding. P. buceroides prefers trees with heights between 10 and 30 meters. Five plant species provide food in the form of nectar and fruit, three species are used for sleeping, and two species are used for nesting. The presence of P. buceroides as an endemic species in NTB plays an important role in maintaining the ecological balance of Moyo Island. Its dependence on various types of vegetation indicates its vital function in forest ecology as well as its potential as an indicator in biodiversity conservation efforts.